The coordinators i and z in Polish: A cognitive-typological approach (Part 2) - Andrason, Alexander (Lingua Posnaniensis, 2017)
Developed within the frame of cognitive and typological linguistics, the present study examines the taxonomical status of the lexemes i and z in Polish. To achieve this aim, the author analyzes the compliance of the two forms with the prototype of coordinate-hood and the structure of their maps of polyfunctionality. The evidence demonstrates that i is a canonical instantiation of the category of coordinate-hood while z is less canonical. Additionally, the two lexemes yield different maps of polyfunctionality (with distinct prototypicality nuclei), which reflects their distinct diachronic and conceptual origin. The map of i radiates from the value of ‘also’ while the map of z radiates from a comitative sense. This article – the last in a series of two – completes the presentation of the empirical evidence and interprets it within the adopted framework. The degrees of canonicity of i and z are determined and the semantic-functional maps of the two lexemes are compared.